Cognitive strategies, motivation to learn, levels of well-being, and risk of dropout: an empirical longitudinal study to qualify ongoing university guidance services. - Jovanice Emily (Global Writing Academica Researching & Publishing, 2023)
The article refers to a longitudinal empirical study that aims to establish the relationship between certain factors that facilitate (or sometimes hinder) academic achievement, such as the motivation to study, the cognitive strategies used and the levels of well-being or discomfort expressed by indicators such as anxiety and depression. Therefore, it aimed to identify the role of these factors in the risk of student dropout. The study was carried out on a sample of 68 self-selected students enrolled in various careers at the